Deliberative Press Speech - Abdulridha, Abbas Ghazy; Mohammed, Nabeel Jassim (Al-Adab Journal, 2021)
The process of making journalistic texts recently take the interest of the researchers that specialized in studying media speech and know how to build journalistic texts and what they carry of linguistic inferences within the text and the inferences related to the external contexts in which they produced in .Thus the researchers study the texts according to the course of critical analysis of the speech and circulated analysis of the speech that concern in study the used language ,what follow that by expose the acts of speech ,its intentions by the inferences of the appeared meanings and their communicative contexts . This research objective is briefed in learn the circulation use in building journal article and the process of producing the speech reaching to analyses the deep building of the intended meaning, learn the role that the context performs in knowing the speaker intentions and objectives through the acts in certain contexts and in social and cultural and political conditions that have strong connection with the conditions of the speech production.The researcher depends on the circulation theory by Austen and Seral (The Speech Act) in order to reach how to build the texts.